The Paradox of Ambition. (June 2017) - Platt, Matthew B.
The last three election cycles suggest that we may be experiencing a surge in black political ambition. Barack Obama's historic election is sandwiched between the failed efforts of people such as Denise Majette, Harold Ford Jr., Artur Davis, and Kendrick Meek. Combined with Cory Booker's senatorial run, scholars have argued that there is a need for a reevaluation of black political ambition and a new classification for black politics itself. If we are experiencing a genuine emergence of a new ambitious breed of black politicians, then the paradox of ambition—that black electoral success is detrimental to black agenda setting—would suggest that we may also be experiencing a major abandonment of black politics. This paper begins to investigate this possibility in terms of individual bill sponsorship for black members of Congress from 1947 to 2010.